Hamartoma lipomatoso pancreático: Reporte de caso y revisión de la literatura - Bravo-Taxa, M (2023)
Pancreatic hamartomas (PH) are extremely unusual non-neoplastic tumor-like lesions and accounts for <1% of all hamartomas. Moreover, there is a distinct variant of PH denominated Pancreatic lipomatous hamartoma (PLH), that is even rarer, with only 5 cases, including the present case, reported in the literature. PLH lacks well-defined features and clinically can be mistaken with other lipomatous lesions of the pancreas, including lipoma, pancreatic lipomatosis, PEComa, liposarcoma, and malignant tumors with lipomatous components. Here, we describe a case of PLH in a 70-year-old male with abdominal pain and a lesion, which was preoperatively diagnosed as a pancreatic no functional low-grade neuroendocrine tumor, and subsequent underwent a laparoscopic enucleation of the tumor. The postoperative pathology and immunohistochemical analyses confirmed the diagnosis of PLH.